Short-Half-Life Chemicals: Maternal Exposure and Offspring Health Consequences—The Case of Synthetic Phenols, Parabens, and Phthalates - Rousseau-Ralliard, Delphine; Bozec, Jeanne; Ouidir, Marion; Jovanovic, Nicolas; Gayrard, Véronique; Mellouk, Namya; Dieudonné, Marie-Noëlle; Picard-Hagen, Nicole; Flores-Sanabria, Maria-José; Jammes, Hélène; Philippat, Claire; Couturier-Tarrade, Anne (Toxics (Basel), 2024)
Phenols, parabens, and phthalates (PPPs) are suspected or known endocrine disruptors. They are used in consumer products that pregnant women and their progeny are exposed to daily through the placenta, which could affect offspring health. This review aims to compile data from cohort studies and in vitro and in vivo models to provide a summary regarding placental transfer, fetoplacental development, and the predisposition to adult diseases resulting from maternal exposure to PPPs during the gestational period. In humans, using the concentration of pollutants in maternal urine, and taking the offspring sex into account, positive or negative associations have been observed concerning placental or newborn weight, children’s BMI, blood pressure, gonadal function, or age at puberty. In animal models, without taking sex into account, alterations of placental structure and gene expression linked to hormones or DNA methylation were related to phenol exposure. At the postnatal stage, pollutants affect the bodyweight, the carbohydrate metabolism, the cardiovascular system, gonadal development, the age of puberty, sex/thyroid hormones, and gamete quality, but these effects depend on the age and sex. Future challenges will be to explore the effects of pollutants in mixtures using models and to identify the early signatures of in utero exposure capable of predicting the health trajectory of the offspring.